Dielectric Permittivity Sensor Based on Planar Open-Loop Resonator - Aquino A. (2021)
Accurate characterization of the dielectric properties of solids and, especially, substrates is crucial for circuitry design and development. For applications requiring low cost, wieldy systems, many attempts have been made involving planar resonant microwave devices. However, most of them have a configuration in which the sample is placed onto the substrate. As a novelty, a structure considering the sample placement into a more sensitive area is presented and analyzed in this letter. The design of this kind of sensors is discussed, and the measurement results are presented. The proposed device is shown to be capable of measuring the full complex permittivity of the sample, and the results compare well with other previous attempts. © 2017 IEEE.